Regulation of miRNA-146a and miRNA-150 Levels by celecoxib in premalignant lesions of K14-HPV16 mice - Gil da Costa, R. M. (2017)
Background/Aim: Human papillomavirus type 16 (HPV16) induces various types of cancer in several locations. Microenvironmental microRNAs (miRNAs) such as miRNA-146a and miRNA-150 regulate cancer-associated inflammation and are involved in HPV-induced carcinogenesis. We studied the effects of celecoxib on the expression of these two miRNAs in HPV16-induced lesions. Materials and Methods: Female transgenic (HPV16+/-) and wild-type (HPV16-/-) mice were administered 75 mg/kg/day celecoxib orally (treatment groups) or placebo (control groups) for four weeks. Skin samples were classified histologically, or used for miRNA analysis by quantitative real-time PCR. Results: HPV16+/- mice showed higher miRNA-146a and miRNA-150 expression levels compared to wild-type animals. Celecoxib further increased miRNA-150 (p<0.05) and miRNA-146a levels in treated animals. Celecoxib-treated HPV16+/- animals also showed reduced incidence of epidermal dysplasia and reduced inflammation, compared to untreated mice. Conclusion: In this model, celecoxib may be able to regulate tumour-associated inflammation, through mechanisms involving the regulation of miRNA-146a and miRNA-150.